Development of an Interactive E-Module Based on Project-Based Blended Learning to Improve Early Childhood Education Teachers’ Pedagogical Content Knowledge and Self-Efficacy in Computational Thinking Training - Cynthia Paramitha Hartono; I Komang Sudarma; Ketut Agustini (Lembaga Bale Literasi, 2026)
Early childhood education (ECE) teachers face a persistent gap in both pedagogical content knowledge (PCK) and self-efficacy when introducing computational thinking (CT) to young children, while existing in-service training tends to be theoretical, time-bound, and inflexible. This study aims to develop an interactive e-module based on project-based blended learning (PjBBL) and to examine its validity, practicality, effectiveness, and user response in CT Training for ECE teachers. The development followed the ADDIE model, with the product deployed on the Google Sites platform and containing four modules delivered through a six-phased PjBBL syntax over 32 training hours in a blended format. Field testing involved 30 ECE teachers in West Denpasar using a one-group pretest-posttest design. Content and media validity were analyzed using Gregory's coefficient; practicality using the User Experience Questionnaire (UEQ); effectiveness using paired-sample t-tests with N-Gain and Hedges' g; and user response using the System Usability Scale (SUS). Results indicated high content validity (0.80) and very high media validity (1.00), as well as Excellent UEQ scores across six scales. The e-module significantly improved PCK (pre-mean = 94.83, post-mean = 114.33; Hedges’ g = 1.666; N-Gain = 0.41, moderate) and self-efficacy (pre-mean = 2.705, post-mean = 3.358; Hedges’ g = 3.161; N-Gain = 0.54, moderate). Findings should be interpreted within the limits of an uncontrolled, single-group design.